Perception of Front-line workers on Covid 19 Vaccination: The Effects, Side effects and Acceptance: Editor's Note: This article has been retracted as of January 2026 as it is out of scope (Indian Journal of Public Health Research & Development, 2023)
AbstractBackground: In 2021 only very few COVID-19 vaccines were anticipated in India. There is lag in vaccination drive& scanty literature on perception of front-line workers on COVID-19 vaccination. The study was planned to get aninsight into vaccination effects, side effects & acceptance.Methods: A cross-sectional study was conducted among front-line workers in a tertiary healthcare institute fromMarch - May 2021 through an online google survey form. The data of the study was collected & analysed usingpercentage.Results: 84% were 21 to 30 years of age, 51% were male. Almost 90.4% had taken 2 doses of vaccination, majorityhad Covaxin (91.5%). 10.6% & 26.5% delayed taking 1st jab & 2nd jab, attributed to fear of side effects, unavailability,tested positive for covid-19. Around 61.7% experienced side effects & majority had myalgia, injection site pain.Most of them perceived it effective in terms of less severity of disease after vaccination. Other prophylacticmeasures included (95.7%) covid precautions, (40.4%) Ivermectin, (25.5%) immune boosters & (18%) homeremedies, 75.5% perceived vaccination as best way to tackle pandemic, whereas 23% stated natural immunity isbetter. 68% vouched for given opportunity to choose their vaccine, 47.9% preferred government setup.Conclusion: All perceived it effective with minimal side effects. Although initially doubtful later showed fullacceptance towards vaccines. Based on evidence study recommends administrative strengthening, provision ofopportunity to choose vaccines, capacity building of vaccinators & vaccine awareness.
Keywords: covid 19 vaccination, perception, side effects.